Successful isolation of a tolerant co-flocculating microalgae towards highly efficient nitrogen removal in harsh rare earth element tailings (REEs) wastewater. (1st December 2019) - Zhang, Yakun; Xiong, Zhensheng; Yang, Liming; Ren, Zhong; Shao, Penghui; Shi, Hui; Xiao, Xiao; Pavlostathis, Spyros G.; Fang, Lili; Luo, Xubiao
Abstract: Acidic rare earth element tailings (REEs) wastewater with high nitrogen and low COD is the most serious and yet unsolved environmental issue in the rare earth mining industry. The effective and cheap remediation of NH4 + -N and NO3 − -N from the REEs wastewater is still a huge challenge. This harsh wastewater environment results in the difficulty for common microbes and microalgae to be survived. In this work, a novel highly tolerant co-flocculating microalgae (the combination of Scenedesmus sp. and Parachlorella sp.) was successfully isolated from the rare earth mine effluent through three-year cultivation. The removal efficiency of total inorganic nitrogen (TIN) by the co-flocculating microalgae cultivation was as high as 90.9%, which is 1.9 times than the average removal efficiency (47.9%) of previously-reported microalgae species in the wastewater with COD/N ratio ranging from 0 to 1. Thus, the residual concentrations of NH4 + -N and TIN could reach the Emission Standards of Pollutants from Rare Earths Industry (GB 26451-2011). Along with the high N removal performance, other related characteristics of the co-flocculating microalgae were also revealed, such as high tolerance towards high NH4 + -N and strong acid, rapid growth and sedimentation, and simultaneous removal of NH4 + -N and NO3 − -N. These algae characteristics were ascribed to the specific co-flocculating community structure covered by extracellular polymeric substances. Graphical abstract: Image 1 Highlights: A novel co-flocculating microalgae was isolated through three-year cultivation. The TIN and NH4 + -N were efficiently removed and lower than the Emission Standard. The simultaneous removal of NH4 + -N and NO3 − -N from the REEs wastewater was achieved. Rapid sedimentation characteristics of the co-flocculating microalgae was revealed.